ANALYSYS OF SLAUTER PRODUCTS PATOLOGY IDENTIFIED BY A VETRINARY EXPERTISE CARRIED OUT AT THE AGRICULTURAL MARKET - Букалова, Н. В.; Приліпко, Т. М.; Якубаш, Р. А. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The article summarizes data of a spreading, reasons and a nosology structure of the farm slaughter products pathology, the dynamics of the cattle and pigs liver disease based on carcasses and internal organs study taken place at the State veterinary laboratory № 15 of Kiev agro market. The investigation was conducted in accordance with «The rules of ante mortem inspection of animals and veterinary-sanitary examination of meat and meat products» approved by the State Department for Veterinary Medicine of Ukraine on 07.06.2002, № 28 registered with the Ministry of Justice of Ukraine on 21.06.2002, № 524/6812. It was registered a frequent appearance of the parasitic lesions such as byfasciolosis, echinococcosis, metastronchilosis and sarkocystosis, in pigs and cattle carcasses that supplied to the market for sale. The author came to a conclusion that possibilities for culling of a slaughtered animals with noninfectious etiology are limited. The data contains only those pathologies that were registered macroscopically. However the data indicates a widespread of lesions among slaughtered dystrophic animals. Therefore according to the result of our research one of the tasks for the state veterinary inspection laboratory professionals at the agro market has to be use of the special research methods at the agro market for a diagnosis of the slaughter products pathology of infectious and noninfectious types.